ANALISIS KUALITAS PELAYANAN PUBLIK DALAM PERSPEKTIF DIGITAL GOVERNANCE (STUDI KASUS DI DESA KEPULUNGAN KECAMATAN GEMPOL) - Khoiriyah, Amanatul; Aminullah, Aminullah (STKIP Pesisir Selatan, 2025)
The Pasuruan Regency Government created a program for Direct Electronic Population Administration Services (e-Pak Ladi Kiosk). The e-Pak Ladi Kiosk was established based on Pasuruan Regent Regulation Number 11 of 2021 concerning Population Administration and Civil Registration Services. The e-Pak Ladi Kiosk is an innovation in population administration services designed to facilitate the community in accessing various services, such as the creation of Family Cards (KK), Identity Cards (KTP), Child Identity Cards (KIA), birth certificates, and death certificates that are technology-based. However, in practice, it is still not optimal. This research aims to analyze the quality of services of the e-Pak Ladi program. The research method used in this study is qualitative and descriptive. The results of this study indicate a low understanding among the community, particularly among the elderly, regarding the digital service system, which leads to a gap in information access and service utilization. Misunderstandings about the concept of 'digital' as an all-in-one fast service also trigger disappointment when technical disruptions occur, such as slow servers or routine app updates almost every month. Socialization strategies through community forums and approaches to students have been implemented, but have not yet reached all layers of society.